Wayside school is falling down ebook - Sachar, Louis (Wayside School, 2017)
Bestselling and Newbery Medal-winning author Louis Sachar knows how to make readers laugh. And there are laughs galore in perennial favorite Wayside School Is Falling Down! Yum! Miss Mush is dishing out her famous Mushroom Surprise in the Wayside School cafeteria. Ron says it tastes like hot dogs and grape jelly. Clean your plate and you'll turn green in time for class picture day. Wear your craziest outfit and you'll fit right in between Maurecia in her striped bikini and Calvin, who's wearing his birthday tattoo. Say cheese! More than fifteen million readers have laughed at the clever and hilarious stories of Wayside School. So what are you waiting for? Come visit Wayside School! Kids 7 to 13 will zoom through these chapter books—laughing their way through the fast, funny, silly but relatable stories. This funny chapter book series includes: Sideways Stories from Wayside School Wayside School Is Falling Down Wayside School Gets a Little Stranger And now also Wayside School Beneath the Cloud of Doom, the brand-new, fourth installment in the series, and the first in twenty-five years!